(untitled) (مجلة العلوم الشاملة, 2025)
The main objective of this research is to study the corrosion rates of carbon steel in low-salinity water, where the total dissolved solids (TDS) does not exceed 15.00 parts per million (ppm). This research was conducted by determining the corrosion rates of carbon steel, measuring the weight loss of carbon steel coupons immersed in water, and studying the effect of pH on reducing the corrosion of carbon steel coupons compared to some well-known chemical compounds, such as NaNO2 and Na3PO4, which are used as corrosion inhibitors in aqueous environments such as cooling systems, water tanks, pipes, pumps, and some other industrial processes. From the results obtained, we concluded that at a pH 10, carbon steel was protected from corrosion, as evidenced by the low corrosion rates. In other words, the expensive chemical compounds used in chemical treatment as corrosion inhibitors could be replaced by adding caustic soda to raise the pH to 10. This would reduce the costs of chemical treatment processes for carbon steel used in low-salinity water systems